(untitled) (Bangladesh Journal of Nutrition, 2013)
A hospital based cross sectional study was carried out among the under-five children admitted to the longer stay wards (LSU) of the hospital of ICDDR,B to investigate the relationship between childrens nutritional status and clinical recovery as well as sock, economic condition. Nutritional status was determined by anthropometric measurements. The study conducted on 94 children of 6-59 months, of whom 49 were malnourished and 49 were well nourished 64 of them were male and 35 were female. (It means that boys are more sufferers in diarrhea than girls.) (Childrens age come within a range of 6-59) month. Mothers education level was lower, 32.6% mothers were illiterate and 40% mothers of malnourished children were illiterate where, 25% mothers having well nourished child were illiterate. Most of the malnourished childrens Family income was below TK. 5,000 per month for majority of the parents whereas, most of the well nourished childrens family income was 8,000tk. It shows that, children having low family income are more likely malnourished than well nourished children. Family member was within 4 persons for majority of the well nourished childrens households. On the other hand family member was more than 5 in out of the malnourished households. Within their limited income; it was difficult to maintain a medium size family properly. Our study reveals that knowledge, attitude and practices of dietary pattern, health, sanitation and immunization of the malnourished childrens family were lower than well-nourished childrens family. Their nutritional knowledge was too low, compared with well nourished childrens parents. In our study, Most of the parents of well-nourished children used to feed colostrums (80.6%) but Parents having malnourished children discarded colostrums (93.6%). Our study reveals that 64.4% malnourished childrens mother has started complementary food in <2 months of age ,on the other hand majority of well-nourished childrens mother gave their child complementary food at the age of 6-9 months. It has been seen that, the majority of well nourished children (62%) were immunized by taking all doses of vaccines. where as most of the malnourished children (49%) has not taken all doses as a result there immunity was lesser than well-nourished children. Most of the caregivers of well-nourished children (43.5%) knows that diarrhea causes by not giving immunization, on the other hand majority of caregiver of malnourished patients (31.9%) knows that main cause of diarrhea is infection by germs. The immunization status of well nourished children was quite satisfactory. 62% well nourished children and only 40% Mal nourished children was completely immunized. It has been seen that, ORS intake was higher in well-nourished children (172.2lml-on the 1st day of hospitalization, compare to malnourished children. Stool output was higher in malnourished children 235.48 ml-on the 1st day after admission. It shows that there is a co-relation between ORS intake, stool output and recovery period. It has been seen that, mean duration of diarrhea before hospitalization was lower in well-nourished children group, but duration of fever, vomiting and abdominal pain rate was higher in this group compared to malnourished group. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14039 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.83-92